Sustainability in the service of science - Keszi-Szeremlei, Andrea (Dunakavics, 2025)
Researchers have been predicting the occurrence, increase in number, and intensification of environmental disasters caused by global warming for years. The leaders of individual countries are gradually becoming aware of this reality. Others have already set out on a path that will transform their countries into more environmentally friendly modes of operation. In order to achieve these goals, target values have been set at both the global and national levels, which, if met, will allow us to avoid or at least slow down the adverse changes predicted by researchers.One of the main causes of global warming is the continuous increase in the carbon dioxide content of the air, for which road transport, and in particular the use of passenger cars, is largely responsible. Transportation using electric vehicles, i.e., electromobility, is one possible solution for replacing vehicles that run on fossil fuels. The popularity of these vehicles has been growing in recent years. The number of electric cars on the world's roads rose from nearly 1 million in 2016 to nearly 14 million by the end of 2023. The popularity of electric cars can be attributed to global reasons as well as economic ones.Electric cars are also becoming increasingly popular in Hungary, with the number of green license plate cars steadily rising, but there are still few purely electric vehicles on Hungarian roads, as the population is not yet willing to take the risks associated with electric cars. The primary objective of the study is to outline, based on perceptions of electric cars, how the population's awareness could be increased, taking into account various possibilities.